(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article examines the interpretation of the image of Zahiriddin Muhammad Babur in Pirimkul Kadyrov’s "Starry Nights" and Flora Annie Steele’s "King-Errant". The descriptions given to Babur as a king and a poet, a warrior, an art and a cultural figure have been reviewed and further enriched by the personal thoughts and opinions of two western and eastern writers.